Pandangan Islam Terhadap Sistem Sosial Patriarki Dalam Rumah Tangga - Hadinata, Arie Bastian (Institut Syekh Abdul Halim Hasan Binjai, 2024)
Patriarchy is a social system that places men as the primary authority and superior to women in various aspects of life. Patriarchy often serves as the basis for Islamic family law, disadvantaging women and hindering gender equality. This article aims to examine Islamic perspectives on patriarchy within the household, particularly in understanding the text of the Qur’an, Surah An-Nisa, verse 34. The study employs a qualitative method with library research and content analysis. The findings indicate that patriarchy within the household is not in line with Islamic teachings, which uphold the dignity and rights of women. The interpretation of Surah An-Nisa, verse 34, that reinforces patriarchal culture must be critically reviewed through contextual and historical approaches. The verse does not grant husbands the legitimacy to coerce wives into domestic roles or to engage in physical violence. A husband’s leadership in the household is a form of care and protection, not authoritarianism or domination. Islam emphasizes the principles of equality and partnership between husband and wife in building a harmonious and happy family.